Place, Personhood and Marginalization: Ontology and Community in Remote Desert Australia - Peterson, Nicolas (Anthropologica, 2015)
Aboriginal Australians living in remote desert communities, usually far from centres of mainstream economic activity and employment, show little inclination to leave them for economic opportunities elsewhere. Some have argued that the tie is based on the ontological significance of place, while others have emphasized marginalization brought about by past government policies. In this article I question both of these views and suggest that emplacement is grounded in the centrality of the relational ontology and the need to live within a dense network of sociality. This raises the issue of whether there are desirable forms of long-term dependency.